Metastatic Basal Cell Carcinoma: A Rare Manifestation of a Common Disease - Paola Piva de Freitas; César Galusni Senna; Mayara Tabai; Carlos Takahiro Chone; Albina Altemani (Case Reports in Medicine)
Introduction. Basal cell carcinoma (BCC) is considered the most common malignancy in Caucasians. It constituted about 80% of all nonmelanoma skin tumors and, despite its high prevalence, is an extremely rare occurrence of metastases, with incidence rates varying from 0.0028% to 0.55%. Case Report. A 58-year-old male patient with BCC on the left nasolabial sulcus for 17 years, reporting 3 previous excisions, evolved with local recurrence. A new procedure was performed, and anatomopathological study confirmed sclerosing BCC. Seven months later, he presented with a mass in the left submandibular region. Combined positron-emission tomography and computed tomography (PET-CT) showed cervical hypercaptation in the left cervical level I and vertebral body of L5. Excision of the cervical lesion was performed with diagnosis of sclerosing BCC compromising the submandibular gland. Biopsy of the lumbar lesion was found to be compatible with bone metastasis. Conclusion. BCC represents a very common entity, and the presence of metastasis, although infrequent, must be proposed because of the greater morbidity and mortality of this complication. This case shows the importance of early diagnosis and intervention in BCC as a way to avoid unfavorable outcomes.